“I'm sick of being called a hero – I want to get paid like one”: Filipino American frontline workers' health under conditions of COVID-19 and racial capitalism - Sangalang, Cindy C. (Frontiers in Public Health, 2022)
Although the era of COVID-19 has reaffirmed the vital role of frontline workers in maintaining a functional society, the ongoing pandemic has taken a devastating toll on their health and well-being. In the United States, Filipino American frontline workers in healthcare and service industries have endured threats to their health, safety, and economic livelihood throughout the pandemic and against the broader backdrop of racialized and xenophobic hate directed toward Asian Americans. Drawing on a qualitative approach, the current study explores work-related health risks and effects of the pandemic for Filipino American frontline workers. Data come from the qualitative arm of a larger mixed-methods study that used a community-based participatory research approach. The current analysis is based on focus group data with thirty-five Filipino American frontline workers, a majority of whom were migrants, that worked across healthcare, caregiving, education, childcare, food services, and retail industries. Situated through the lens of racial capitalism, themes included: (1) work-related stress, tensions, and trauma, (2) anti-Asian racism and intersections with age- and gender-based violence, and (3) working while ill and distressed. Study findings can inform interventions and policies to improve health, occupational environments, and labor conditions in order to support minoritized communities disproportionately affected by COVID-19.